(untitled) (Anclajes, 2012)
One of the key elements of the rhetorics of Antiquity was puritas. Puritas consists of grammatical correctness in linguistic expression, it is the locutionary quality which tends to maintain the uncontaminated purity of language. This linguistic phenomenon presents from the end of the twentieth century an untimely normative effort in the context of a postmodern era marked by the uncontrollable flows of persons and languages, a phenomenon that is clearly reflected in all its complexity and its constitutive tensions in the gestation and evolution of hybrid languages such as Spanglish and the subsequent production of marginal literary systems like nuyorican poetry. The nuyorican poetry of authors such as Tato Laviera (1951 -) sets a rhetoric of Spanglish as a language of extraterritoriality and interstitiality, a rhetoric of impurity and delight that becomes a "minor literature" in its Deleuzian sense.